Protective effects of Spirulina (Arthrospira Platensis) on In Vitro Fertilization (IVF) and embryo development in female mice treated with cyclophosphamide - Golchin Mousavi; Shapour Hasanzadeh; Hasan Malekinejad; Gholamreza Najafi (Fasa University of Medical Sciences, 2018)
Background & objective: Cyclophosphamide is an extensively used chemotherapeutic agent against wide varieties of neoplastic ailments, which has been known to cause ovarian damages and infertility in mammals. The purpose of this study is to investigate the protective effects of Spirulina platensis on in vitro fertilization (IVF) and embryo development in adult mice exposed to Cyclophosphamide. Material & methods: 40 adult female mice were divided into 8 groups each comprised 5 animals. The first group was considered as control. The groups 2, 3 and 4 were exposed to Spirulina at rates of 200, 400 and 800 mg/kg respectively through oral route, daily for 28 days. The 5th group receive cyclophosphamide (150 mg/kg, ip) in a single-dose. Groups 6, 7 and 8 received cyclophosphamide and Spirulina together with aforementioned doses. In vitro fertilization and embryo development were assessed in all groups at the end of experiment. Results: The groups which received Spirulina at rates of 200, 400 mg/kg beside cyclophosphamide in comparison to group which received merely cyclophosphamide, the number of oocytes, percentages of fertilization, two-cell embryos, blastocysts and hatched embryos were reduced significantly (p<0.05). In fertilization, two-cell embryo, but at dose of 800 mg/kg was not able to reduce damages brought by cyclophosphamide. Conclusion: According to the results of this study, spirulina encourages protective effects on cyclophosphamide induced reprotoxicity on In Vitro Fertilization approach.